2021
DOI: 10.1101/2021.08.12.456080
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate Mediates Adiponectin Receptor Signaling Essential For Lipid Homeostasis And Embryogenesis

Abstract: Cells and organisms require proper membrane composition to function and develop. Phospholipids are the major component of membranes and are primarily acquired through the diet. Given great variability in diet composition, cells must be able to deploy mechanisms that correct deviations from optimal membrane composition and properties. Here, using unbiased lipidomics and proteomics, we found that the embryonic lethality in mice lacking the fluidity regulators Adiponectin Receptors 1 and 2 (AdipoR1/2) is associat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 89 publications
(168 reference statements)
0
4
0
Order By: Relevance
“…At higher concentrations, similar to those measured in plasma from patients on FFA-rich diet 9 , 10 (and at which we found that EA is toxic; Figure 4B ), membrane fluidity was decreased ( Figure 5C ). Exposure to PA led to linear regions of increased rigidity reminiscent of the ER 71 , 72 ( Figure S3E ), while EA induced distinct spherical regions of increased rigidity reminiscent of lipid droplet morphology ( Figure S3E ). These observations are consistent with robust EA incorporation into TAGs ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…At higher concentrations, similar to those measured in plasma from patients on FFA-rich diet 9 , 10 (and at which we found that EA is toxic; Figure 4B ), membrane fluidity was decreased ( Figure 5C ). Exposure to PA led to linear regions of increased rigidity reminiscent of the ER 71 , 72 ( Figure S3E ), while EA induced distinct spherical regions of increased rigidity reminiscent of lipid droplet morphology ( Figure S3E ). These observations are consistent with robust EA incorporation into TAGs ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…RNF145's lipid-modulating effects are intimately linked to its ability to target lipid metabolic enzymes for degradation [75,[79][80][81][82] . Accordingly, RNF145's substrates include the ER-resident lipid hydrolase adiponectin receptor 2 (ADIPOR2) and the cholesterol biosynthetic enzyme HMGCR [75,[79][80][81] .…”
Section: Rnf145mentioning
confidence: 99%
“…ADIPOR2 has an inverted 7-TMD G-protein coupled receptor topology and is structurally and catalytically similar to ceramidases of the CREST superfamily [103][104][105] . Its ceramidase activity may partially explain its function, inducing sphingosine-1-phosphate-mediated activation of PPAR𝛄 or SREBP1 through sphingosine-1-phosphate receptors and transcriptional upregulation of lipid metabolic enzymes including the lipid desaturase SCD1 [82,106] . However, many aspects relating to the molecular function and regulation of ADIPOR2 remain unclear such as how ADIPOR2 senses and responds to PA-induced stress in the absence of an ilgr-2 orthologue [81] .…”
Section: Adipor2 -An Er-resident Lipid Hydrolase Regulating Membrane ...mentioning
confidence: 99%
See 1 more Smart Citation